Spiritual and Communal Harmony Through Tarawangsa Traditional Art - Meylani, Hilda; Hernawan, Wawan (Journal of Contemporary Rituals and Traditions, 2024)
Purpose of the Study: This research explores how Tarawangsa Art, as a traditional cultural practice, plays a crucial role in strengthening communal identity and spirituality within the Budi Daya community in Cibedug, Lembang, West Java, Indonesia. Methodology: The study adopts a qualitative approach through participatory observation and in-depth interviews with community members, traditional leaders, and practitioners of Tarawangsa Art. Main Findings: The findings reveal that Tarawangsa Art not only acts as an expression of culture and spirituality but also as a crucial pillar in nurturing the community's identity and social cohesion. Integrating cultural expressions, spiritual values, and social dynamics forms a strong foundation for communal togetherness. Additionally, the community's adaptability and resilience in maintaining this tradition demonstrate cultural flexibility and robustness in the face of modernization. Applications of this Study: These findings provide insights for policymakers, educational practitioners, and cultural preservation institutions on the importance of supporting Tarawangsa Art preservation initiatives. Novelty/Originality: This study offers a new perspective on the role of Tarawangsa Art in maintaining communal identity and cohesion in the era of globalization. Through in-depth research on this cultural practice, the study highlights how spirituality and community are interwoven in creating unique cultural adaptations amidst social and economic changes.